WW3C mobile web best practices evaluation of an educational website - Díaz, Francisco Javier
This article presents the experience of a heuristic evaluation on the mobile website of the National University of La Plata, UNLP, based on the recommendations of the World Wide Web Consortium, W3C, for this type of interface. It also includes a brief reference to the methodology used during the development process, in which prototyping evaluations had a leading role, taking into account the specific characteristics for being both an educational a mobile website. The evaluation took place through two mechanisms, a manual human revision an automatized validation. This concluded with endless problems errors discovered through both mechanisms. They are being analyzed solved in order to achieve the quality of use required in the final version of the mobile website.